2010
DOI: 10.1016/j.jaci.2009.12.016
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the dust mite allergen Der p 7 reveals similarities to innate immune proteins

Abstract: Background-Sensitization to house dust mite allergens is strongly correlated with asthma. Der p 7 elicits strong IgE antibody and T-cell responses in mite allergic patients. However, the structure and biological function of this important allergen are unknown. Allergen function may contribute to allergenicity as shown for the protease activity of Group 1 mite allergens and the interaction with the innate immune system by Group 2 mite allergens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
95
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 64 publications
3
95
0
Order By: Relevance
“…For example, Der p 2 functionally substituted for murine MD-2, an innate immune protein known to bind a lipopolysaccharide-binding protein from Gram-negative bacteria (18). Similarly, the structure of Der p 7 resembles lipopolysaccharide-binding protein, and Der p 7 was shown to bind a lipopeptide from Gram-positive bacteria (17). The structure of Der p 5 presented here suggests that a Der p 5 dimer may also have a propensity to bind hydrophobic compounds.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…For example, Der p 2 functionally substituted for murine MD-2, an innate immune protein known to bind a lipopolysaccharide-binding protein from Gram-negative bacteria (18). Similarly, the structure of Der p 7 resembles lipopolysaccharide-binding protein, and Der p 7 was shown to bind a lipopeptide from Gram-positive bacteria (17). The structure of Der p 5 presented here suggests that a Der p 5 dimer may also have a propensity to bind hydrophobic compounds.…”
Section: Discussionmentioning
confidence: 80%
“…Recently, crystallographic studies revealed that Der p 7 was distantly related to hydrophobic ligand-binding proteins of the human innate immune system (17); this relationship was not previously identified from sequence information alone. It was suggested that Der p 7 may co-opt the innate immune response into promoting allergenicity through the binding and delivery of hydrophobic ligands (17), as has been demonstrated for the mite allergen Der p 2 (18).…”
mentioning
confidence: 97%
“…They all contain conserved LBP/BPI domains. In this regard, Fel d 8 is similar to the group 7 allergens of HDMs [27]. Neither latherin nor Der p 7 have been shown to bind enterobacterial LPS, but Der p 7 has been shown to bind the lipopeptide polymyxin B.…”
Section: Discussionmentioning
confidence: 99%
“…The group 7 structures show these uniquely Arachnida proteins to be members of the LPS-binding/bactericidal permeability inducing proteins 47,48 with similarities to insect odorant binding proteins that include hormone receptors. 49 They have elongated structures with antiparallel beta-sheets wrapped around a helix to create a lipid-binding domain.…”
Section: Group 7 Allergensmentioning
confidence: 99%